TBC1D7 Mutations are Associated with Intellectual Disability, Macrocrania, Patellar Dislocation, and Celiac Disease. Issue 4 (April 2014) - Alfaiz, Ali Abdullah; Micale, Lucia; Mandriani, Barbara; Augello, Bartolomeo; Pellico, Maria Teresa; Chrast, Jacqueline; Xenarios, Ioannis; Zelante, Leopoldo; Merla, Giuseppe; Reymond, Alexandre
ABSTRACT TBC1D7 forms a complex with TSC1 and TSC2 that inhibits mTORC1 signaling and limits cell growth. Mutations in TBC1D7 were reported in a family with intellectual disability (ID) and macrocrania. Using exome sequencing, we identified two sisters homozygote for the novel c.17_20delAGAG, p.R7TfsX21 TBC1D7 truncating mutation. In addition to the already described macrocephaly and mild ID, they share osteoarticular defects, patella dislocation, behavioral abnormalities, psychosis, learning difficulties, celiac disease, prognathism, myopia, and astigmatism. Consistent with a loss‐of‐function of TBC1D7, the patient's cell lines show an increase in the phosphorylation of 4EBP1, a direct downstream target of mTORC1 and a delay in the initiation of the autophagy process. This second family allows enlarging the phenotypic spectrum associated with TBC1D7 mutations and defining a TBC1D7 syndrome. Our work reinforces the involvement of TBC1D7 in the regulation of mTORC1 pathways and suggests an altered control of autophagy as possible cause of this disease.